Qualidade da assistência pré-natal em Nampula, Moçambique - Muleva, Belarmina Reis (Universidade de São Paulo, 2020)
A realização da consulta pré-natal de alta qualidade está diretamente relacionada aos melhores indicadores maternos e fetais e à prevenção de morbimortalidade materna. Em Moçambique, estudos sobre assistência pré-natal mostram que a maior parte das mulheres fez pré-natal, mas apenas metade fez as quatro ou mais consultas preconizadas pelo Ministério da Saúde. Além disso, as gestantes têm se apresentado aos centros de saúde para fazerem sua primeira consulta pré-natal somente no final do segundo trimestre da gestação. Essas questões mostram que a qualidade da assistência ao pré-natal é ainda um desafio, embora haja poucos estudos sobre o tema naquele contexto. Objetivo: Avaliar a qualidade da assistência pré-natal entre as mulheres do município de Nampula, em Moçambique. Método: Trata-se de um estudo quantitativo, do tipo transversal, realizado no município de Nampula, em Moçambique, na África. A amostra constou de 393 mulheres de 18 a 49 anos, com parto ocorrido em maternidade ou no domicílio no segundo semestre de 2019. As entrevistas foram conduzidas por meio de instrumento estruturado, aplicado face-a-face, até 15 dias após o parto. A qualidade da assistência pré-natal foi analisada com base nas diretrizes do Ministério da Saúde de Moçambique. A qualidade do pré-natal foi categorizada em inadequada e adequada. Modelos de regressão logística múltipla foram conduzidos para analisar os aspectos associados a ter realizado pré-natal adequado. Resultados: As mulheres participantes do estudo tinham, em média, 26 anos de idade, e metade tinha ensino primário (52,4%). Embora todas as mulheres tenham realizado o pré-natal, apenas 13,0% tiveram o pré-natal classificado como adequado. Mulheres que realizaram pré-natal em gestações anteriores (OR=4,28; IC95%=1,45-12,62) e com gravidez planejada (OR=2,51; IC95%=1,11-5,68) foram as que tiveram mais chance de ter um pré-natal adequado. Observou-se que a assistência pré-natal não atendeu ao que é preconizado, como a idade gestacional de início do pré-natal, número mínimo de consultas a serem feitas, realização de alguns exames (hemograma, glicemia, tipagem sanguínea e fator Rh) e oferta de orientações sobre sinais de risco e de parto. Quanto à satisfação com a assistência pré-natal recebida, mais da metade das mulheres mostrou-se insatisfeita com o tempo de espera para ser atendida pela profissional de saúde. Conclusão: De modo geral, os critérios preconizados para que uma assistência ao pré-natal seja de alta qualidade não estão incorporados na prática clínica no município de Nampula.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

The Price of a Green Conscience - Brown, Jasmine; Ewald, Jonas; Fritz, Heiko (Linneaus University, 2020)
Scholars and civil society organizations have over the last decade referred to large-scale carbon sequestration TPPs as "carbon colonialism" (Carmody and Taylor, 2016) as well as a "development by dispossession" dressed in new clothing behind words such as climate change mitigation and development (Kröger, 2012). Concerns have been raised that the trade-offs from the implementation of industrial tree plantations (ITPs) may result in conflicting effects on countries' overall development (The Oakland Institute, 2019; Osborne, 2015; Nel & Hill, 2013). Moreover, NGO's and think tanks, such as FIAN (2012) and the Oakland Institute (2017, 2019), have released reports in which such tree planting projects are accused of displacing people and violating human rights (FIAN, 2012; The Oakland Institute, 2017, 2019; Carmody & Taylor, 2016). This thesis explores the impacts of carbon forestry projects, emphasizing the impacts of ITPs on local livelihoods and their subsequent effects on development. Three dimensions have been chosen to limit the scope of this thesis: (1) food security; (2) access to land; and (3) employment & income. The thesis is conducted using a qualitative desk study and secondary analysis of two multiple case studies of Uganda and Mozambique. The findings presented suggest carbon forestry projects may negatively affect all three dimensions, ultimately affecting communities' sustainable development. The author recommends further research to evaluate the complex effects of carbon forestry projects.
Keywords: *snowball; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; poverty / pobreza

The political economy of regional hydropower investments in Africa - Eyita-Okon, Ekeminiabasi (2020)
Africa has abundant potential to generate hydroelectric power. Yet with an uneven record of building large dams, much of this potential remains untapped. This thesis addresses the question of why some large dam projects have been built and others have not. The problem of credible commitment by host governments to prospective investors is central to the explanation. The problem is that while large dam projects require large investments over lengthy periods, after construction is complete host governments may face strong temptations to renege on their agreements with investors –in an environment that lacks a supranational authority to enforce agreements. Anticipating this, investors will be reluctant to invest, and many potentially mutually beneficial hydroelectric dams will go unbuilt. The empirical part of the thesis begins with a statistical analysis of hydroelectric potential and realised capacity in Africa compared to other regions. This is followed by comparative case studies of the Cahora Bassa dam in Mozambique, completed in 1974, and the Grand Inga dam in the Democratic Republic of Congo (DRC), still unbuilt despite plans stretching back decades. I show that the credible commitment problem in the Cahora Bassa case was overcome through strategic interaction between the Portuguese colonial host government and the South African apartheid government, which was the main investor and the principal consumer of the power generated. The credible commitment problem in the Grand Inga case has been much more intractable due to the larger numbers of investors and consuming countries involved, and importantly to political risk within the DRC. The thesis contributes to the understanding of how Africa can better exploit its hydroelectric potential, in an era of increasing emphasis on renewable energy sources
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura

Accessing global value chains: The politics of promoting export-driven industrialisation and upgrading in the Mozambican cashew processing industry - Saulich, Christina Lisa (2020)
Successful export sectors in manufacturing and agribusiness are important drivers of structural transformation in Sub-Sahara African countries. Backed by industrial policies and active state involvement, a small number of successful productive export sectors has emerged in Sub-Saharan Africa. This thesis asks the question: How do politics shape the promotion of export-driven industrialisation and firm-level upgrading in Sub-Saharan Africa? It exemplifies this question with an in-depth, qualitative study of the cashew processing industry in Mozambique in the period from 1991 until 2019. Mozambique used to be one of the world’s largest producers and processors of cashew nuts in the 1960s and 1970s. At the end of the 20th century, the cashew processing industry broke down completely but has re-emerged as one of the country’s few successful agro-processing exports. The thesis draws on theoretical approaches from the fields of political science, notably the political settlements framework, global value chain analysis and the research on technological capabilities to explore why the Mozambican Government supported the cashew processing industry and how Mozambican cashew processors acquired the technological capabilities needed to access the global cashew value chain and to upgrade. It makes an important theoretical contribution by linking the political settlements framework and the literature on upgrading in global value chains to study how politics shaped productive sector promotion and upgrading in the Mozambican cashew processing industry. The findings of the thesis are based on extensive primary data, including 58 expert interviews and 10 firm surveys, that was collected in Mozambique in 2018 as well as a broad base of secondary literature. The thesis argues that the Mozambican Government supported the cashew processing industry because it became important for the Government’s political survival. Promoting the cashew sector formed part of an electoral strategy for the ruling FRELIMO coalition and a means to keep FRELIMO factions united by offering economic opportunities to key constituencies. In 1999, it adopted a protectionist cashew law that created strong incentives for cashew processing in Mozambique. This not only facilitated the re-emergence of the cashew processing industry after its breakdown. The law and the active involvement of the National Cashew Institute (INCAJU) also affected the governance of the local cashew value chain, the creation of backward linkages, and the upgrading paths of cashew processors. The findings of the thesis suggest that the cashew law reduced the pressure on the cashew processing industry to upgrade. The law further created opportunities for formal and informal rent creation for members of the political elite and lower level FRELIMO officials that prevented a far-reaching reform of the law. The thesis shows that international buyers do not promote upgrading among Sub-Sahara African firms in global value chains with market-based or modular governance. Moreover, firms that operate in countries where industrial policies are not enforced effectively cannot draw on the support of government institutions to enhance their capabilities and to upgrade. Firms therefore mainly depended on costly learning channels at firm level, e.g. learning by doing or hiring skilled labour, and/or on technical assistance from donors to build the technological capabilities needed to access global value chains and to remain competitive. The findings of the thesis suggest that researchers, governments, development practitioners and consultants need to rethink their understanding of upgrading in GVCs in four ways. First, they need to move away from understanding upgrading in terms of moving towards more complex, higher value-added activities in GVCs (functional upgrading). Instead, it is important to consider the potential of other, more realistic types of upgrading for firms in low-income countries, such reducing risks by diversifying suppliers and buyers or increasing rewards by making production processes more efficient. Second, they need to replace an overly positive view on upgrading that neglects possible side-effects at sector and/or country level. Third, GVC participation on its own does not promote upgrading among local supplier firms in Sub-Saharan Africa. The interests of lead firms and Sub-Sahara African supplier firms may not be aligned or even conflicting. Targeted industrial policies and the creation of institutions that effectively promote capability building among firms therefore become even more important. Finally, upgrading needs to be understood as a process that is not only shaped by interactions between firms, but also by local domestic politics. The findings of the thesis are highly relevant for scholars from the fields of political science, development studies, and economics. Its practical implications and tools, e.g. a technological capabilities matrix for the cashew industry, are of interest for development practitioners, members of public institutions in Sub-Sahara African countries, local entrepreneurs, and representatives of local business associations that are involved in promoting export sectors and upgrading among local firms.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura